Antibacterial effectiveness of red fruit extract (Pandanus conoideus Lam) against S.mutans as an acrylic resin based denture cleanerr: Efektivitas antibakteri ekstrak buah merah (Pandanus conoideus Lam) terhadap S.mutans sebagai pembersih gigi tiruan berbasis resin akrilik - Silvia Naliani; Patricia Octaviane Mellinia Sutarto P; Vinna Kurniawati Sugiaman; Jane Amelia Vebriani Wibisono (Makassar Dental Journal, 2023)
Streptococcus mutans are bacteria in denture base plaque; therefore antibacterial ingredients are needed in denture cleaners. Red fruit (Pandanus conoiedeus Lam) from Papua has several secondary metabolites that can be used as antibacterial. This study is intended to determine the minimum inhibitory concentration (MIC) and minimum kill concentration (MKC) of red fruit extract (RFE) against S.mutans as an acrylic resin-based denture cleaner using 96% ethanol solvent. With broth microdilution technique and 10% DMSO solvent, MIC was measured for 8 concentrations: 100%, 75%, 50%, 25%, 12.5%, 6.25%, 3.123%, 1,563% and chlorhexidine 0.2% as positive control. Furthermore, the MKC test was carried out using total plate count method and one-way Anova analysis with Post Hoc Tukey to determine significant differences between treatments. As a result, there were no MIC and MKC, because RFE have active compounds that are unable to penetrate the biofilm wall of S.mutans. It is con-cluded that RFE has no inhibitory and killing effect on the growth of S.mutans, so it cannot be used to determine the MIC and MKC. While the 0.2% CHX gluconate has an inhibitory and killing effect on S.mutans bacteria with an average killing power of 100%.